2014
DOI: 10.3390/v6041637
|View full text |Cite
|
Sign up to set email alerts
|

Generation of West Nile Virus Infectious Clones Containing Amino Acid Insertions Between Capsid and Capsid Anchor

Abstract: West Nile virus (WNV) is a positive-sense RNA arbovirus responsible for recent outbreaks of severe neurological disease within the US and Europe. Large-scale analyses of antiviral compounds that inhibit virus replication have been limited due to the lack of an adequate WN reporter virus. Previous attempts to insert a reporter into the 3’ untranslated region of WNV generated unstable viruses, suggesting that this region does not accommodate additional nucleotides. Here, we engineered two WNV infectious clones c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…However, the instability or decreased fitness of the recombinant viruses compared to the parental virus limit their application in some experimental designs, as noted by Aubry et al (2015). This instability in engineered virus expressing reporter genes was also reported in other flavivirus and DNA virus platforms (Song et al 2012, Vandergaast et al 2014, Zhang et al 2015.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…However, the instability or decreased fitness of the recombinant viruses compared to the parental virus limit their application in some experimental designs, as noted by Aubry et al (2015). This instability in engineered virus expressing reporter genes was also reported in other flavivirus and DNA virus platforms (Song et al 2012, Vandergaast et al 2014, Zhang et al 2015.…”
Section: Discussionsupporting
confidence: 61%
“…Zhang et al (2015) reported the construction of a West Nile Virus (WNV) expressing GLuc and its use in neutralization assays, but the recombinant virus gradually lost stability along the passages, where GLuc activity was no longer detected in passage 3. Vandergaast et al (2014) also found similar instability in a GLuc-expressing WNV. The lower stability of these recombinant viruses in relation to YFV-GLuc probably is due to the insertion position GLuc gene (within C gene) and/or to the pathogenic strain used as backbone of WNV-GLuc, especially in Vandergaast et al (2014).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, none of a stable luciferase protein-based WNV reporter virus has been available for measuring neutralizing antibody, though several WNV reporter viruses were developed (Deas et al, 2005;McGee et al, 2010;Pierson et al, 2005;Vandergaast et al, 2014). In this study, we have developed a stable WNV reporter virus using Gaussia luciferase as a reporter gene, which has a higher enzymatic activity compared with Renilla luciferase (Tannous et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…passages (Vandergaast et al, 2014). Similarly, a C-terminal GFP tag of Sindbis virus's RdRp failed to infect cells, but virus was viable when the tag was switched to 3|FLAG (Cristea et al, 2010).…”
Section: Tap-tagged Dengue Virus and Host-virus Interactionsmentioning
confidence: 99%